Impact Analysis of Infrastructure Changes from Signalized Intersection to Underpass on Vehicle Exhaust Emissions - Rallya Napinia Tarigan; M. Ridwan Anas; Ahmad Perwira Mulia; Gina Cynthia Raphita Hasibuan; Johannes Tarigan (Newinera Publisher, 2025)
The Medan City Government plans to make infrastructure changes by building underpass at the existing signalized intersection between Road Ir. H. Juanda and Road Brigjend. Katamso to reduce traffic congestion. In recent years, vehicle emissions have become a global concern due to their significant impact on public health and environmental quality. As road traffic and vehicle numbers continue to grow, transportation has become a key contributor to air pollution from vehicle exhaust emissions. Consequently, it is essential to assess whether the infrastructure changes from signalized intersection to underpass have an impact on vehicle exhaust emissions. The impact analysis of infrastructure changes on vehicle exhaust emissions is evaluated through traffic simulation using PTV Vissim software with two scenarios, namely the do nothing scenario (existing signalized intersection) and the do something scenario (underpass) ), focusing on CO, NOx, and VOC emissions. The comparative results indicate substantial changes: CO emissions declined by 42.5% (from 40,991 grams to 23,567 grams), VOC by 37.1% (from 9,500 grams to 5,975 grams), while NOx emissions increased by 23.3% (from 7,075 grams to 8,725 grams). These findings suggest that the infrastructure changes from signalized intersection to underpass can positively influence air quality by reducing specific pollutants. However, further studies are necessary to examine its broader impact on other types of vehicle exhaust emissions using diverse emission categories, multiple calculation approaches, and various analytical methods for comprehensive comparison.